Economic Contributions from Industrial Mining in Madagascar - World Bank Group (World Bank, Washington, DC, 2015)
The contribution of mining used to be seen essentially through taxes and royalties; it tends to be viewed now in a more integrated manner. This report, the result of a 2-year research project, attempts to improve that information and to structure the debate around the long term economic impact of industrial mining. The objectives of this research were to assess the fiscal and non-fiscal contribution of mining to Madagascar economy, and by so doing to reinforce the capacities of main stakeholders to prepare for the related challenges and opportunities. Its scope was deliberately focused on large-scale mining, excluding i) mining exploration; ii) artisanal and small-scale mining; and iii) quarrying. This explains why the reader may notice important differences between historical data and information published by EITI in Madagascar, which also includes petroleum exploration activities. The research focused on economic spillovers as a first step. Admittedly, additional research on the environmental and social impacts of industrial mining over time should complement this work to provide for a more complete picture of the contribution of the sector towards sustainable development.